Firebreaks: Poems - Kinsella, John (2016)
Known for a poetry both experimental, “activist,” and lyrical that reinvents the pastoral, John Kinsella considers his and his family’s life at Jam Tree Gully, in the Western Australian wheatbelt, and his deeply felt ecological ...